Specific Plasma MicroRNA Signatures in Predicting and Confirming Crohn's Disease Recurrence: Role and Pathogenic Implications. Issue 10 (25th October 2021) - Moret-Tatay, Inés; Cerrillo, Elena; Hervás, David; Iborra, Marisa; Sáez-González, Esteban; Forment, Javier; Tortosa, Luis; Nos, Pilar; Gadea, Jose; Beltrán, Belén
Abstract : INTRODUCTION: MicroRNAs (miRNAs) are important epigenetic regulators in Crohn's disease (CD); however, their contribution to postoperative recurrence (POR) is still unknown. We aimed to characterize the potential role of miRNAs in predicting POR in patients with CD and to identify their pathogenic implications. METHODS: Of 67 consecutively operated patients with CD, we included 44 with pure ileal CD. Peripheral blood samples were taken before surgery and during follow-up. The patients were classified according to the presence or absence of POR assessed by ileocolonoscopy or magnetic resonance imaging enterography. The miRNAs were profiled by reverse transcription polymerase chain reaction before surgery and during morphological POR or, for those who remained in remission, 1 year after surgery. R software and mirWalk were used. RESULTS: Five human miRNAs (miR-191-5p, miR-15b-5p, miR-106b-5p, miR-451a, and miR-93-5p) were selected for discriminating between the 2 patient groups at presurgery (PS), with an area under the curve of 0.88 (95% confidence interval [0.79, 0.98]). Another 5 (miR-15b-5p, miR-451a, miR-93-5p, miR-423-5p, and miR-125b-5p) were selected for 1 year, with an area under the curve of 0.96 (95% confidence interval [0.91, 1.0]). We also created nomograms for POR risk estimation. CCND2 and BCL9L genes were related to PS miRNA profiles; SENP5 and AKT3 genes were related to PS and 1 year; and SUV39H1 and MAPK3K10 were related to 1 year. DISCUSSION: Different plasma miRNA signatures identify patients at high POR risk, which could help optimize patient outcomes. We developed nomograms to facilitate the clinical use of these results. The identified miRNAs participate in apoptosis, autophagy, proinflammatory immunological T-cell clusters, and reactive oxygen species metabolism. Abstract :